Kajian Pemanfaatan Ruang Kawasan Kanal Banjir Timur - hendradi, Fajar Henradi; Ayub Muktiono; Rajagukguk, jenni Ria (Magister Kajian Pembangunan Perkotaan dan Wilayah, 2023)
The need for public green open space is increasing along with urban development and population growth. The existence of green open space development around river/canal areas currently has the potential to increase the availability of green open space in DKI Jakarta. One of the green open space areas in the riverside/canal area built by the government is the East Flood Canal area, which is partly located in Duren Sawit District, East Jakarta. The purpose of this research is to formulate a strategy for structuring the East Flood Canal area of Duren Sawit District in accordance with zoning regulations and regional characteristics. From analysis that has been done, the compatibilty between the planning and existing conditions are partially not prominent, therefore in the next can be done with a more humanist concept such as Waterfront City. To achieve this concept, strategies that can be taken with optimizing spatial planning of built area such as urban structure plan implementation and urban development incentive, keeping the function East Flood Canal as Green Open Space with revitalization of existing functions of catchment area and Recreational Waterfront development , promoting of the development plan in order to attract privates, and trying to involve local community (public participatory) in relocating parking and the five-foot way trader.